Orthopaedic registries with patient-reported outcome measures. Issue 6 (June 2019) - Wilson, Ian; Bohm, Eric; Lübbeke, Anne; Lyman, Stephen; Overgaard, Søren; Rolfson, Ola; W-Dahl, Annette; Wilkinson, Mark; Dunbar, Michael
Abstract : Total joint arthroplasty is performed to decreased pain, restore function and productivity and improve quality of life. One-year implant survivorship following surgery is nearly 100%; however, self-reported satisfaction is 80% after total knee arthroplasty and 90% after total hip arthroplasty. Patient-reported outcomes (PROs) are produced by patients reporting on their own health status directly without interpretation from a surgeon or other medical professional; a PRO measure (PROM) is a tool, often a questionnaire, that measures different aspects of patient-related outcomes. Generic PROs are related to a patient's general health and quality of life, whereas a specific PRO is focused on a particular disease, symptom or anatomical region. While revision surgery is the traditional endpoint of registries, it is blunt and likely insufficient as a measure of success; PROMs address this shortcoming by expanding beyond survival and measuring outcomes that are relevant to patients – relief of pain, restoration of function and improvement in quality of life. PROMs are increasing in use in many national and regional orthopaedic arthroplasty registries. PROMs data can provide important information on value-based care, support quality assurance and improvement initiatives, help refine surgical indications and may improve shared decision-making and surgical timing. There are several practical considerations that need to be considered when implementing PROMs collection, as the undertaking itself may be expensive, a burden to the patient, as well as being time and labour intensive. Cite this article: EFORT Open Rev 2019;4 DOI: 10.1302/2058-5241.4.180080